Symbolism in Modernist Poetry: A Comparative Study of Ezra Pound and Wallace Stevens - Fatma Abdul Ruhman Almoadab (Journal of Scientific and Human Dimensions, 2026)
This study explores how symbolism works in modernist poetry through a comparison between Ezra Pound and Wallace Stevens. Rather than treating symbolism as a single, unified technique, it suggests that it may be more useful to think of it as a range of practices shaped by different artistic and philosophical concerns. Pound’s poetry often reflects Imagist principles, relying on precise and concrete imagery, while Stevens tends to move toward a more abstract and reflective mode that focuses on perception and the way reality is constructed. Through close readings of selected poems, the study considers how these different approaches engage with key aspects of modern experience, including fragmentation, uncertainty, and the search for meaning. It also suggests that, despite their differences, the symbolic practices of both poets overlap in important ways. In this sense, symbolism appears less as a fixed device and more as an ongoing process of meaning-making.